2022
DOI: 10.3389/fmicb.2022.803121
|View full text |Cite
|
Sign up to set email alerts
|

A Two-Time Point Analysis of Gut Microbiota in the General Population of Buenos Aires and Its Variation Due to Preventive and Compulsory Social Isolation During the COVID-19 Pandemic

Abstract: The COVID-19 pandemic poses a great challenge to global public health. The extraordinary daily use of household disinfectants and cleaning products, social distancing and the loss of everyday situations that allow contact between individuals, have a direct impact on the transfer of microorganisms within the population. Together, these changes, in addition to those that occur in eating habits, can affect the composition and diversity of the gut microbiota. A two-time point analysis of the fecal microbiota of 23… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 102 publications
1
9
0
Order By: Relevance
“…However, the F/B ratio presents high variability among studies, since Mariat et al (100) reported 0.6, while Vaiserman et al (103) detected 1.42 for older adults and, in the present study, the F/B ratio decreased 52.5% (4.36 ± 5.35 to 2.29 ± 1.65) after physical distancing (medium effect size), which could be related to increase in age-associated Bacteroidetes, as described by Martinez et al (102). This result is discordant with Aguilera et al (19), which showed that F/B ratio in the pre-pandemic period was 1.01 ± 0.38 and, after five years (during the physical distancing period), it increased to 1.47 ± 0.96. The age of participants, methodological approaches and interval between sampled periods may justify the differences between these results.…”
Section: Frontiers Insupporting
confidence: 53%
See 3 more Smart Citations
“…However, the F/B ratio presents high variability among studies, since Mariat et al (100) reported 0.6, while Vaiserman et al (103) detected 1.42 for older adults and, in the present study, the F/B ratio decreased 52.5% (4.36 ± 5.35 to 2.29 ± 1.65) after physical distancing (medium effect size), which could be related to increase in age-associated Bacteroidetes, as described by Martinez et al (102). This result is discordant with Aguilera et al (19), which showed that F/B ratio in the pre-pandemic period was 1.01 ± 0.38 and, after five years (during the physical distancing period), it increased to 1.47 ± 0.96. The age of participants, methodological approaches and interval between sampled periods may justify the differences between these results.…”
Section: Frontiers Insupporting
confidence: 53%
“…In fact, these alterations contribute to microbiome imbalance with deleterious consequences for the host ( 16 ), increasing dysbiosis of gut microbiome in older adults. There is a paucity of information about the microbiome of South American populations, since most studies were performed in European, Asian and North American populations, that differ in genetic background, eating habits and environmental factors ( 19 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Current pandemic control measures have been proposed to have large, uneven and potentially long-term detrimental effects on the human microbiome globally with strict implementation of social distancing, extensive hygiene measures, restricted travel and other measures that influence overall microbial loss 157 . A small study comparing pre-pandemic gut microbiota of 23 healthy individuals from Buenos Aires, Argentina, and its variation during social isolation found a significant ( P <0.05) decrease in phylogenetic diversity and in the phylum Verrucomicrobiota, which contributes to intestinal health and glucose homeostasis, during isolation 158 . The COVID-19 pandemic has been associated with a markedly lower Actinobacteria (Actinomycetota) richness, higher Bacteroidetes (now known as Bacteroidota) richness, and an altered abundance of antibiotic-resistance genes in faecal samples collected from 32 healthy individuals before and during the first wave of the pandemic 159 .…”
Section: Consequences On the Human Microbiomementioning
confidence: 99%